Archaeological Ethnography of the Battle of Aslıhanlar (29–30 August 1922): A Case Study of Public Archaeology, Visual Storytelling, and Interactive Map Design. (February 2016) - Aksoy, Can; Bayar, Ziyacan
Abstract : Our article seeks to determine the functions of visual communication design through the lens of modern conflict and public archaeologies. The Battle of Aslıhanlar, which took place in the triangle of the villages of Çal Köy, Allıören, and Yüğlük in Kütahya from 29 to 30 August 1922, was the focus of our experimentation. Our archaeological survey project was carried out in 2013; interviews with local people, a review of the literature available and our observations of local myths and traditions that emerged after the war constitute the basis of our article. We categorized these sources for the project design in order to form a storytelling narrative, so that the viewer could participate in the process of conflict as well as the ongoing research. We foresaw three major challenges while categorizing this complex dataset: equivalence of visual language; variable outputs of the multi-dimensional research methods; and interactivity for creating a live social platform. We responded to these challenges by developing a graphic design concept and an interactive map of the data. Our design surrounds the viewer with a historical timeline, which includes all of our research findings in one interactive interface.